PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PERUM BULOG DIVRE PONTIANAK - B11109148, RENI APRIANTI (Jurnal Manajemen Update, 2013)
Compensation is one factor affecting performance employees. Compensation is divided into two parts: compensation and financial non financial compensation. The main goal of this research is to find out the influence of compensation and financial compensation for non financial performance by employees bulog divre pontianak. In the research, first researchers used form research descriptive is a form of research devoted to describe fenomena-fenomena existing good natural phenomena and phenomena fabrications. This phenomenon it might be form, activity, characteristic of, change, relations, in common and differences between the phenomenon the one with phenomena other. Second, researchers used research causal method is search empirik that systematic where researcher cannot control variable a free because the incident has occurred or because it cannot be manipulated. The regression coefficient of the variable standards of financial Compensation (X 1) is 0,726 and is positive with the significant value of 0.000, i.e. If there is an increase in independent variable compensation non financial (X 2) then the value of the performance (Y) as the dependent variable will also increase. There is a positive relationship between financial Compensation and performance, so that the greater the financial compensation that is given, then the performance of employees will also increase. The regression coefficient of the variable compensation standard of non financial (x 2) is (-0,010) is negative and significant value of 0,936. Meaning if there is a decrease in variable compensation non financial (X 2), then the value of the performance (Y) will increase. The relationship was negative, sehinggga if the non financial compensation given to decline, then the value of the employee's performance will be increased from a negative value to his increasingly given compensation coefficient of nonfinansial. Keywords: Financial Compensation, NonFinancial Compensation, Performance